Toward an international health workforce data standard: an analysis of regulatory agency documents. (2018) - Opalek, Amy; Greenberg, Jane
Agencies responsible for regulating health professionals require detailed data describing individual practitioners and their qualifications. Initial collection of these data allows agencies to determine whether health professionals are qualified to practise safely. Ongoing collection of practitioner data is also critical for ensuring an adequate supply of health workers. A metadata standard facilitating data sharing among regulatory agencies can support these needs, providing the infrastructure necessary for detailed, interoperable practitioner registries. This paper presents the results of a document analysis of application forms used by 20 international agencies to collect data about physicians seeking licensure/registration. This research yielded over 250 unique data elements in 15 categories of interest. Though the scope of data required by regulatory agencies is vast, this research revealed a set of common metadata properties that provided a base for an international standard to support interoperable registries and the global exchange of health practitioner data.